Новые археологические материалы послеурартского времени на территории западной Армении (Турция) и их место в истории древнеармянской культуры - Тирацян, Г. A. (1976)
Tiracjan/Tirazian, Gework; New archaeological finds of post-Urartian period in Western Armenia (Turkey) and their place in the history of ancient Armenian culture; engl. Résumé S. 293-295.